Hubungan Pengetahuan Dan Sikap Ibu Tentang Pemenuhan Gizi Seimbang Balita Dengan Asupan Dan Status Gizi Balita Di Posyandu Desa Gunung Katun Tanjungan Kecamatan Tulang Bawang Udik Kabupaten Tulang Bawang Barat Tahun 2024 - Cika, Yuriska; Ai Kustiani, Ai Kustiani (Universitas Prima Indonesia, 2024)
Nutritional problems in Indonesia are still an unresolved problem, from year to year the number of nutritional problems always exists. According to SKI, 2023 the prevalence of nutritional status of toddlers in West Tulang Bawang, toddlers who experience stunting is 10.5%, wasting is 7.1%, underweight is 9.7%, and overweight is 2.7%. This study uses a correlation analytical research design with a cross-sectional approach, a population of 69 with a total sample of 41 samples, the sampling technique used is Probability Sampling with simple random sampling, data collection using questionnaires and food recall, data analysis is Univariate and Bivariate (Chi square test). The results of the study showed that there was a significant relationship between maternal knowledge and attitudes about fulfilling balanced nutrition for toddlers with toddler intake at the Posyandu, Gunung Katun Tanjungan Village, Tulang Bawang Udik District, West Tulang Bawang Regency (p = 0.000). From the research results, it is recommended that health workers in the Gunung Katun Tanjungan Village area are able to optimize the balanced nutrition counseling program for toddlers to improve the knowledge and attitudes of mothers to pay more attention to the intake and nutritional status of their toddlers. Keywords: Intake, Knowledge, Attitude and Nutritional Status of Toddlers